2003
DOI: 10.1007/s00421-003-0953-9
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and autonomic activity at rest and during exercise in various physiological conditions

Abstract: The rhythmic components of heart rate variability (HRV) can be separated and quantitatively assessed by means of power spectral analysis. The powers of high frequency (HF) and low frequency (LF) components of HRV have been shown to estimate cardiac vagal and sympathetic activities. The reliability of these spectral indices, as well as that of LF/HF ratio as a marker of autonomic interaction at rest and during exercise, is briefly reviewed. Modifications in autonomic activities induced by different physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
293
3
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(341 citation statements)
references
References 39 publications
(72 reference statements)
25
293
3
11
Order By: Relevance
“…Previous studies in young (32) and middle-aged subjects (32,33) have demonstrated alterations in HRV indices due to postural changes. Other investigators have reported that these changes lose their statistical significance with advancing age (34,35). The cross-sectional design of this study is a limitation, since the characteristics of the autonomic control of HR in postmenopausal women prior to the use of estrogen therapy were not known.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies in young (32) and middle-aged subjects (32,33) have demonstrated alterations in HRV indices due to postural changes. Other investigators have reported that these changes lose their statistical significance with advancing age (34,35). The cross-sectional design of this study is a limitation, since the characteristics of the autonomic control of HR in postmenopausal women prior to the use of estrogen therapy were not known.…”
Section: Discussionmentioning
confidence: 93%
“…Assessment of HRV is a standardized, non‐invasive method for quantification of autonomic function and thus recommended for the evaluation of subclinical and manifest CAN in diabetes (Pumprla et al. 2002; Perini & Veicsteinas 2003; Spallone et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the LF/HF ratio reflects the balance of the autonomic nervous system. Perine et al [9] examined these parameters in healthy people during exercise, at a controlled respiration, and changes of body position. The authors believe that spectral parameters do not reflect increase of sympathetic and decrease of parasympathetic contribution during exercise.…”
Section: сLinical Medicinementioning
confidence: 99%
“…Different mechanisms of arterial pressure control are likely to be involved in these situations. LF are known to be partly caused by the activity of baroreflex when the rate of cardiac contraction is decelerated if pressure in the aorta increases [9]. Billman [12] shows in his work that it is impossible to physiologically interpret this common index.…”
Section: сLinical Medicinementioning
confidence: 99%